What is a Good Visualization for Digital Humanities Researchers? An Exploratory Study. Issue 1 (13th October 2021) - Ma, Rongqian; Xiao, Fanghui
Abstract: Visualization in digital humanities (DH) has developed into a charged topic as increasing numbers of humanities researchers begin to work with machine‐readable data. The current research literature on DH visualization has primarily approached the subject from a theoretical perspective, arguing the humanistic visualization should fundamentally differ from scientific visualization to represent the distinct nature of humanities data and inquiries. However, few studies have tried to empirically understand what it means to be a good visualization for humanities researchers and practitioners. This study aims to bridge this research gap by offering an exploratory investigation into researchers' perceptions on visualization, particularly how they evaluate a visualization in humanities research. Through 10 semi‐structured interviews with humanities scholars engaging in digital work, our study demonstrates that perceptions of a quality visualization among the humanities researchers are closely related to researchers' purposes of using visualization and their self‐confidence in visualization knowledge and skills. This study serves as a baseline for future empirical research on DH visualization and potentially informs the best practices for humanistic visualizations.